THE RELEVANCE OF THE USE OF MEDIA IN FOREIGN LANGUAGE TEACHING (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the advantages of using different media in teaching foreign languages, the integration of information and communication technologies in the traditional educational process. The work also presents a selection of current English-language publications, their versions in electronic format, as well as Internet sites of international public information TV channels and news agencies. With the advent of digital platforms, the nature of modern media has changed; they have ceased to be one-pronged. The author emphasizes the exceptional effectiveness of the use of authentic material and a wide range of topics covered in periodicals, the linguistic relevance of mass media resources, their informative saturation for the formation of skills and abilities of interlingual and intercultural communication.